Kontribusi Sikap Kreatif Siswa, Variasi Gaya Mengajar Guru, Dan Lingkungan Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP Muhammadiyah 4 Surakarta - Dewi, Isnaini Lutfiana, Rita Pramujiyanti Khotimah, S.Si, M.Sc (2017)
This study was conducted with the objectives, (1) to examine the contribution of students creative attitude, variation of teacher's teaching style, and learning environment to mathematics learning outcomes, (2) to examine the contribution of students' creative attitude toward mathematics learning outcomes, (3) to examine the contribution of variation of teacher's teaching style toward mathematics learning outcomes, (4) to examine the contribution of learning environment toward mathematics learning outcomes. Type of this research is quantitative with the research subject of all students grade VIII SMP Muhammadiyah 4 Surakarta, amounting to 152 students, while 110 students as the sample. The sampling technique used proportional random sampling method. Dara collection used questionnaires and documentation. Data analysis used multiple linear regression with 5% significance level. The research results obtained, (1) there was a contribution of students creative attitude, variation of teacher's teaching style, and learning environment to mathematics learning outcomes, (2) there was a contribution of students' creative attitude toward mathematics learning outcomes, (3) there was not a contribution of variation of teacher's teaching style toward mathematics learning outcomes, (4) there was a contribution of learning environment toward mathematics learning outcomes. Keywords: mathematics learning outcomes, learning environment, creative attitude, variation of teacher's teaching style